THE RELATIONSHIP BETWEEN LONELINESS LEVEL AND DECEPTION TENDENCIES IN MARRIED INDIVIDUALS - Demir, Yasin; Kumcağız, Hatice (Fırat University, 2020)
This study was conducted to investigate the relationship between the level of loneliness and the tendency to deceive in married individuals. 270 volunteer married individuals participated in the study. The data of the study were collected by using the Deception Tendency Scale and UCLA Loneliness Scale and the analyzes were performed through SPSS package program. Results show that males' tendency to deceive is significantly higher than females, and loneliness level does not differ significantly according to gender. Both the tendency of deception and loneliness levels of the individuals who had multiple marriages were significantly higher than the individuals who had single marriages. In addition, there was a positive relationship between loneliness and tendency to deceive. Finally, it was found that the tendency to deceive predicts loneliness to a meaningful level.

Bu araştırma evli bireylerde yalnızlık düzeyi ile aldatma eğilimi arasındaki ilişkinin incelenmesi amacıyla gerçekleştirilmiştir. Araştırmaya 270 gönüllü evli birey katılmıştır. Araştırmanın verileri Aldatma Eğilimi Ölçeği ve UCLA Yalnızlık Ölçeği kullanılarak toplanmış ve analizler SPSS paket programı aracılığıyla yapılmıştır. Bulgular; erkeklerin aldatma eğilimlerinin kadınlardan anlamlı düzeyde yüksek olduğunu, yalnızlık düzeyinin cinsiyete göre anlamlı düzeyde farklılaşmadığını göstermektedir. Birden fazla evlilik yapan bireylerin hem aldatma eğilimleri hem de yalnızlık düzeyleri tek evlilik yapan bireylerden anlamlı düzeyde yüksektir. Ayrıca yalnızlık ile aldatma eğilimi arasında pozitif yönde ilişki olduğu saptanmıştır. Son olarak aldatma eğiliminin yalnızlığı anlamdı düzeyde yordadığı saptanmıştır.
THE RELATIONSHIP BETWEEN LONELINESS LEVEL AND DECEPTION TENDENCIES IN MARRIED INDIVIDUALS